Comprehensive Review of Quality Improvement Strategies in Pediatric Healthcare - OMRAN, DR ABEER SAEED; ALSAYAT, JOUF YOUSEF; KASHMIRI, MOHAMMED EMAD; BINMUHAREB, ABDULMAGED KHALED; ALMUTIRI, JAWAHER MARZOUQ; ALRESHIDI, REEM EID FAHAD (Journal of Ecohumanism, 2024)
Children’s healthcare systems experience some specific issues for which successful QI interventions to foster patient safety, treatment efficacy, and overall pediatric care need to be developed. The concern of this review is QI approaches like the Lean model, Six Sigma, and patient-centered approaches, which have many presumed advantages that embody the minimization of hospitalization, chronic illness management, and family involvement. The use of technology, including EHR, has reduced medical mistakes; alternatively, chronic care programs, including telehealth and family involvement, have enhanced medication compliance and further improved results. Other care models focused on families and communicating with the patient have added to the patient's satisfaction levels. Nevertheless, lack of staff cooperation, scarcity of resources, and variable patient profiles remain the major challenges to the spread of integrated care. To overcome those challenges, there must be a deliberate effort to allocate resources and train people, use artificial intelligence, and use real-time big data technologies. This review discusses the significance of implementing appropriate QI approaches for enhancing pediatric healthcare and offers numerous lessons for enhancing pediatric care, mainly for stakeholders, including providers, policymakers, and researchers interested in promoting the health of children.